Pengaruh Gaya Kepemimpinan Terhadap Motivasi Kerja Karyawan di Pabrik Kelapa Sawit (Studi Kasus Pada PT. Flora Wahana Tirta Rifansi Kabupaten Kampar) - Imroatun Fadillah; Rosmayani Rosmayani (Pelantar Press, 2024)
The purpose of this study is to analyze, find out, and explain the influence of leadership style on employee motivation in palm oil mills (case study on Pt. Flora Wahana Tirta Rifansi, Kampar Regency). The type of research used by the author is a descriptive survey and uses quantitative research methods using SPSS 26 software. The population in this study is an employee of PT: Flora Wahana Tirta Rifansi, Kampar Regency which totaled 55 respondents. The results of this study show that in the leadership style variables with indicators of instructive behavior, consultative behavior, participatory behavior, negative behavior, and supportive leadership behavior, the respondents agreed. As for the work motivation variable with behavioral direction indicators, the level of effort and persistence obtained the results of respondents with the category of agree. Then from the statistical calculation, it was found that the leadership style had a significant effect on the work motivation of employees at the PT. Flora Wahana Tirta Rifansi, Kampar Regency.